AGILE DEVELOPMENT OF THE RE-QUEST INCENTIVE-BASED SURVEY APPLICATION: ENSURING ETHICAL FAIRNESS IN DATA COLLECTION - Asoka Syukur, Pramudya; Miftach Fakhri , M.; Nirmala S, Aprilianti; Miftahul Jannah , Devi; Nurjannah, Elma; Dio Nurul Awalia, Andi (Jurusan Pendidikan Teknik Elektro, 2025)
Low response rates in digital surveys due to survey fatigue and challenges in maintaining data quality. To develop an incentive-based survey application using the Agile method to enhance participation and data quality. The study used the Agile methodology within the framework of the Software Development Life Cycle (SDLC), focusing on iterative sprints for planning, analysis, design, implementation, and testing using the Black Box method to ensure application functionality and reliability. The